Playing hard: Dispute Boards vs Emergency Referee - Paredes Carbajal, Gustavo (2020)
In the context of construction disputes under clause 20 of FIDIC contractual models, this article analyzes a very particular situation of conflict between the functions of a dispute boards and the powers of an emergency arbitrator and its implications in the contract.